Philosophy and Engineering: Reflections on Practice, Principles and Process
XIX, 431 p. 42 illus.
Keywords: Building on the breakthrough text Philosophy and Engineering: An Emerging Agenda, this book offers 30 chapters covering conceptual and substantive developments in the philosophy of engineering, along with a series of critical reflections by engineering practitioners. The volume demonstrates how reflective engineering can contribute to a better understanding of engineering identity and explores how integrating engineering and philosophy could lead to innovation in engineering methods, design and education. The volume is divided into reflections on practice, principles and process, each of which challenges prevalent assumptions and commitments within engineering and philosophy. The volume explores the ontological and epistemological dimensions of engineering and exposes the falsity of the commonly held belief that the field is simply the application of science knowledge to problem solving. Above all, the perspectives collected here demonstrate the value of a constructive dialogue between engineering and philosophy and show how collaboration between the disciplines casts light on longstanding problems from both sides. The chapters in this volume are from a diverse and international body of authors, including philosophers and engineers, and represent a highly select group of papers originally presented in three different conferences. These are the 2008 Workshop on Philosophy and Engineering (WPE-2008) held at the Royal Academy of Engineering; the 2009 meeting of the Society for Philosophy and Technology (SPT-2009) at the University of Twente in the Netherlands; and the Forum on Philosophy, Engineering, and Technology (fPET-2010), held in Golden, Colorado at the Colorado School of Mines.